Implementasi Sistem Kendali dan Monitoring Keamanan Pintu Berbasis IoT Menggunakan Perangkat Mobile - Tengku Nopriyanti Murti; Ikhwan Ruslianto; Uray Ristian (STMIK Budi Darma, 2022)
One of the important things in the management of the lecture building is the need for a security system to lock the door. This is necessary to avoid the possibility of theft and negligence in opening or closing the door at certain hours. The purpose of this study is to implement an Internet of Things-based door security control and monitoring system using a mobile device. This system is a substitute for door security that uses conventional locks. The system can be accessed by setting the operating time from 07.00-17.00. If there is a change in operational time, the admin can reset the operational time. Before the operating time ends, the speaker gives an automatic door lock warning, and the door is automatically locked and cannot be accessed. In addition, the system is equipped with a door alarm using a buzzer and a notification is sent via the application when the door is forcibly opened. The door control process starts by reading the operating time and the status of the door lock solenoid. If the initial status of the door lock solenoid is locked, the RFID tag sends data to the RFID reader, then the door lock solenoid opens. The test results show that the response time for opening and locking doors using RFID is 26,22 seconds and 22,25 seconds. The response time to open and lock the door using the application is 5,03 seconds and 5,34 seconds, respectively. The average response time when the door is forcibly opened is 14,83 seconds